Pulmonary hypertension due to left heart disease: updated Recommendations of the Cologne Consensus Conference 2011 - Rosenkranz, Stephan; Bonderman, Diana; Buerke, Michael; Felgendreher, Ralf; Ten Freyhaus, Henrik; Grünig, Ekkehard; de Haan, Fokko; Hammerstingl, Christoph; Harreuter, Alexander; Hohenforst-Schmidt, Wolfgang; Kindermann, Ingrid; Kindermann, Michael; et al. (International journal of cardiology, 2011)
The 2009 European Guidelines on Diagnosis and Treatment of Pulmonary Hypertension (PH) have been adopted for Germany. While the guidelines contain detailed recommendations regarding pulmonary arterial hypertension (PAH), they contain only a relatively short paragraph on other, much more frequent forms of PH including PH owing to left heart disease. The guidelines point out that the drugs currently used to treat patients with PAH (prostanoids, endothelin receptor antagonists and phosphodiesterase type 5 inhibitors) have not been sufficiently investigated in other forms of PH. However, despite the lack of respective efficacy data an uncritical use of targeted PAH drugs in patients with PH associated with left heart disease is currently observed at an increasing rate. This development is a matter of concern. On the other hand, PH is a frequent problem that is highly relevant for morbidity and mortality in patients with left heart disease. It that sense, the practical implementation of the European Guidelines in Germany requires the consideration of several specific issues and already existing novel data. This requires a detailed commentary to the guidelines, and in some aspects an update already appears necessary. In June 2010, a Consensus Conference organized by the PH working groups of the German Society of Cardiology (DGK), the German Society of Respiratory Medicine (DGP) and the German Society of Pediatric Cardiology (DGPK) was held in Cologne, Germany. This conference aimed to solve practical and controversial issues surrounding the implementation of the European Guidelines in Germany. To this end, a number of working groups was initiated, one of which was specifically dedicated to PH due to left heart disease. This commentary describes in detail the results and recommendations of the working group which were last updated in October 2011.